(untitled) (Annals of Medical Research, 2021)
Aim: Although ectopic pregnancy is defined as the implantation of the fertilized egg outside the uterine cavity, even today it remains to be an important health problem. In this study, we aimed to evaluate retrospectively demographic characteristics, diagnosis, and treatment modalities in patients diagnosed as ectopic pregnancy.